Helicobacter pylori Infection in Idiopathic Chronic Urticaria - Grace Nami Sianturi; Evita H Effendi; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Helicobacter pylori (Hp) infection is the most common chronic bacterial infection in human. The role of Hp infection in various GI disorders had been widely accepted. However, further studies have found new extragastrointestinal involvement such as urticaria. Chronic urticaria is a common disorder that has complex pathophysiologic mechanism. As mater of fact, etiology remains unclear in most of the cases. This condition is called Idiopathic Chronic Urticaria. Several studies had shown high prevalence of Hp infection in patients with ICU and improved symptoms after eradication therapy of Hp. This observation had suggested that Hp has important role as etiologic factor in some cases of ICU. The presence of Hp infection and its role in ICU should be proven before initiating eradication therapy, so that irrational used of drugs and antibiotics resistance can be prevented. Keywords: Helicobacter pylori, Idiopathic Chronic Urticaria